2020
DOI: 10.1136/ijgc-2020-001783
|View full text |Cite
|
Sign up to set email alerts
|

Fertility considerations prior to conservative management of gynecologic cancers

Abstract: Fertility-sparing management of early-stage gynecologic cancers is becoming more prevalent as increasing evidence demonstrates acceptable oncologic and reproductive outcomes in appropriately selected patients. However, in the absence of randomized controlled trials, most of the commonly used treatment algorithms are based only on observational studies. As women are increasingly postponing childbearing, the need for evidence-based guidance on the optimal selection of appropriate candidates for fertility-sparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Table 1 summarizes the participants, materials, and findings of each scale development step. Literature review indicated that oncofertility decision making is multifactorial, depending on cancer characteristics and treatment, sociodemographic characteristics, decision-making characteristics, reproductive histories, self-care and lifestyle factors, and psychosocial factors 25–33. Nine papers focused specifically on survivors’ fertility needs, concerns, and experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the participants, materials, and findings of each scale development step. Literature review indicated that oncofertility decision making is multifactorial, depending on cancer characteristics and treatment, sociodemographic characteristics, decision-making characteristics, reproductive histories, self-care and lifestyle factors, and psychosocial factors 25–33. Nine papers focused specifically on survivors’ fertility needs, concerns, and experiences.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of patients with EC for fertility-sparing treatment is important in order to achieve the best outcomes. Current guidelines recommend progestin therapy in stage IA, grade 1 (well-differentiated) endometrioid-type endometrial cancer [ 24 , 25 ].…”
Section: Criteria For Fertility-sparing Treatment In Endometrial Cancermentioning
confidence: 99%
“…The 2018 National Comprehensive Cancer Network (NCCN) includes the following criteria to consider fertility-sparing management of endometrial cancer: well-differentiated (grade 1) endometrioid endometrial carcinoma [ 19 ]; disease thought to be limited to the endometrium on magnetic resonance imaging (preferred) or ultrasound; absence of suspicious or metastatic disease on imaging [ 19 , 25 , 26 , 27 ]. Table 1 shows the optimal indications for fertility-sparing treatment.…”
Section: Criteria For Fertility-sparing Treatment In Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the type I tumours respond to progestins. 5,[9][10][11][12] The national comprehensive cancer network (NCCN) guidelines were followed in most of the cases except a few patients with myometrial invasion who were not willing for definitive surgery. 5 Patients were thoroughly informed that fertility sparing treatment is not the standard of care for endometrial carcinoma management.…”
mentioning
confidence: 99%